Transformation of Ecology-Based Islamic Education in Pesantren Communication Aalysis in Internalizing Environmental Values - Muhamad Hanif Fuadi (Fahmina: Jurnal Pendidikan Islam, 2026)
This study investigates how internal communication patterns in Eco Pesantren Daarut Tauhiid Bandung a nationally recognized Adiwiyata-awarded institution shapes the transformation of Islamic ecological doctrine into embodied social practice. Employing communication ethnography (three weeks of participant observation, in-depth interviews with ten purposively selected informants across hierarchical positions, and systematic analysis of twenty-three institutional documents), data were analyzed through Hymes' SPEAKING model, reflective thematic analysis, and Rogers' diffusion of innovation framework. Three dominant communication patterns emerge: (1) religious hierarchical communication, through which the kiai's spiritual authority legitimizes ecological values via theological framing, generating compliance but producing structural dependency; (2) horizontal collaborative communication, which encourages participatory innovation but remains vulnerable to voice suppression; and (3) ritualization of environmental communication, which integrates ecological messages into Islamic rituals and daily practice but risks ritual hollowing when meaning renewal is absent. The study also maps specific forms of institutional resistance theological skepticism, selective compliance, and instrumentalization of eco-religious framing alongside the structural conditions that produce communicative failures. These findings demonstrate that sustained behavioral change is highest under conditions of integrated spiritual legitimacy, participatory ownership, and ongoing meaning renewal. Theoretically, the study contributes a Triadic Model of Islamic Ecological Education Communication Spiritual Legitimacy, Social Participation, and Value Ritualization that extends organizational communication theory to faith-based hierarchical contexts. Practically, the model offers replicable guidelines for green pesantren program design, emphasizing distribution of communicative legitimacy, institutionalization of participatory forums, and systematic renewal of ecological ritual meaning.